KEMAMPUAN ADAPTABILITAS HASIL SEJUMLAH VARIETAS UNGGUL PADI DI TIGA LINGKUNGAN YANG BERBEDA DI GUNUNGKIDUL - Bambang Sutaryo (Universitas Muhammadiyah Purwokerto, 2014)
Yield Adaptability for Some Superior Rice Varieties in the Three Difference Zones at Gunungkidul, namely North, Midle, and South Zones was studied during the wet-season (WS) of 2012/2013. The locations in each three zones were : a) Ngawen 300 m asl, and b) Patuk 250 m asl (North), c) Playen 175 m asl, and d) Karangmojo 150 m asl (Midle), e) Ponjong 200 asl and Tepus 250 m asl (South). Six new superior rice varieties, namely Inpago 5, Inpari 7, Inpago 8, Inpari 10, Inpari 11 and Inpari 19 and a previous populair varieties such as Situ Bagendit was used in this trial. The experiment was designed using randomized complete block design with three replicatioins. Data indicated that the highest yield adaptability was found in Inpari 19, Inpago 8 and Situ Bagendit indicated by yield stability with relatively small deviation from regressions (0.15, 0.08, and 0.17, respectively), meanwhile Inpari 10, Inpari 11, Inpago 5 and Inpari 7 possessed low yield adaptability indicated by yield instability with big and significantly different deviation from regressions (3.86*, 3.96*, 2.86* and 2.98*, respectively).The highest average yield was obtained by Inpari 19 (6.42 ton ha-1) and followed by Inpari 10 (6.02 ton ha-1), and Inpari 11 (5.78 ton ha-1). The highest environment index for grain yield was found at Playen (Midle Zone, 0.73), Patuk and Ngawen (North Zone, 0.62 and 0.60 respectively). Keywords: adaptability, environment, new superior varieties, rice